The Behavior of Strength Properties from Three Different Tree Boles of Aras in Sarawak - Gaddafi, Ismaili; Badorul Hisham, Abu Bakar; Khairul Khuzaimah, Abdul Rahim (UNIMAS Publisher, 2011)
Aras had been selected and tested in small clear specimens. Sampling of test specimens are made from three sections of the tree bole namely from bottom, middle, and top parts. This paper looks into the information of strength properties from three sections of sampled. The strength properties test required are the modulus of rupture, modulus of elasticity and compression stress parallel to grain. Meanwhile, the physical properties' test referred to moisture content and basic density. The testing conducted in two different conditions of the trees, which were referred to green and air-dry condition. It was found that the average mean values for modulus of rupture, modulus of elasticity and compressive stress parallel to grain tested at green condition were 47.52N/mm2, 6358.56N/mm2 and 22.42N/mm2 respectively meanwhile at air-dry condition were 70.49N/mm2, 8217.64N/mm2 and 34.07N/mm2 respectively. Meanwhile, the average mean values for moisture content at green condition were 83.34% whilst at the air-dry condition were 12.33%. Basic density remains unchanged from both conditions.